International Admissions: Ethical Challenges - Zaretsky, Daniel (International Higher Education, 2013)
The May 2013 NACAC Report concludes that the paying by colleges of commission fees to education agents, while acceptable, is not a best practice as it promotes misrepresentations to students. The Report overlooks the more troubling incentives: agent misrepresentations to gouge genuine but easily manipulated students for large fees, or conniving with students (or their parents) to abet fabrication of student academic records. Addressing these challenges requires ardent institutional accountability.